2019
DOI: 10.3390/cancers11030360
|View full text |Cite
|
Sign up to set email alerts
|

Arytenoid Fixation in Laryngeal Cancer: Radiological Pictures and Clinical Correlations with Respect to Conservative Treatments

Abstract: Background: The aim of this retrospective study was to identify different radiological features in intermediate–advanced laryngeal cancer (LC) associated with arytenoid fixation, in order to differentiate cases still safely amenable to conservative treatment by partial laryngectomy or chemoradiotherapy. Methods: 29 consecutive patients who underwent open partial horizontal laryngectomies (OPHLs), induction chemotherapy followed by radiotherapy in the case of >50% response (IC + RT) or total laryngectomy wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
1
6
0
4
Order By: Relevance
“…These three scenarios carry a different prognosis in terms of functional and oncologic outcomes. 28 Cricoarytenoid fixation is considered a limit for TOLMS and it could be corroborated in our series, where a lower local control was found in those patients with cricoarytenoid impairment. However, posterior radiologic PGS involvement may be present without arytenoid impairment.…”
Section: Discussionsupporting
confidence: 84%
“…These three scenarios carry a different prognosis in terms of functional and oncologic outcomes. 28 Cricoarytenoid fixation is considered a limit for TOLMS and it could be corroborated in our series, where a lower local control was found in those patients with cricoarytenoid impairment. However, posterior radiologic PGS involvement may be present without arytenoid impairment.…”
Section: Discussionsupporting
confidence: 84%
“…We found that it significantly related to impaired vocal cord motility and radiological evidence of sclerosis of the arytenoid cartilage 4 . The recent literature confirmed the negative prognostic meaning of such posterior spread of glottic cancer to the cricoarytenoid joint and associated arytenoid fixation 6 . A change of TNM classification (from T3 to T3b) have already been suggested as a result 1 .…”
Section: Discussionmentioning
confidence: 72%
“…The recent literature in the sphere of laryngeal surgical oncology has increasingly focused on the anatomical space delineated by the thyroid, cricoid and arytenoid cartilages [1][2][3][4][5][6][7] , which we refer to as the "thyro-cricoarytenoid space" (TCAS). The inferior paraglottic space (PGS) is a submucosal compartment bound laterally by the laryngeal cartilaginous framework and medially by the vocal muscle 8 .…”
Section: Introductionmentioning
confidence: 99%
“…As a decision aid, Succo et al differentiated four patterns of vocal cord fixation: patients with fixation of the arytenoid by weight effect (pattern I) or involvement of the posterior paraglottic space, spreading towards the crico-arytenoid joint, and with infraglottic extension ≤ 10 mm (pattern II) were safely manageable by pCRT. Patients with involvement of the crico-arytenoid joint and infraglottic extension >10 mm (pattern III) and massive crico-arytenoid unit involvement reaching the hypopharyngeal mucosa (pattern IV) should undergo upfront TL [ 41 ].…”
Section: Discussionmentioning
confidence: 99%